Analisis Minat dan Partisipasi Siswa dalam Olahraga Bola Basket - Agum Bako; Anugrah Hutabarat; Irvan Plaston Simanjuntak; Iwan Tober Manullang; Sunaryo Sutanto Purba (Badan Penerbit STIEPARI Press, 2025)
This research aims to find out how students' interest and participation in basketball in the secondary school environment. Data collection was carried out using an online questionnaire distributed to 35 students from Meda The research results show that the majority of students have a high interest in basketball, but their active participation is influenced by various factors such as the availability of facilities, free time, and the support of friends. This research concludes that to increase student involvement in basketball, it is necessary to strengthen infrastructure and consistent coaching from the school.